LANGUAGE DISORDER IN SPEAKING ENGLISH AT ISLAMIC BOARDING SCHOOL: PSYCHOLINGUISTIC ANALYSIS - Nasution, Ummi Aisah; Daulay, Sholihatul Hamidah (Universitas PGRI Sumatera Barat, 2023)
The aim of this research article is to find out some language disorders in speaking English especially at Islamic boarding school. The researcher uses a descriptive qualitative method. The researcher also uses observation in the female students' dormitory environment regarding how to use English as their daily language and interviews to find answers about the factors of female students’ English speaking problems as data collection techniques to 4 female students at Darul ‘Adaalah Islamic boarding school dormitory. The result of this research is students got some difficulties in their speaking English which consist of linguistic problems and psychological problems. In linguistic problems, students have difficulty in lack of pronunciation and vocabulary. In psychological problems, students have difficulty in lack of confidence, anxiety and shyness.